2021
DOI: 10.1186/s12890-021-01770-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum interleukin-17 predicts severity and prognosis in patients with community acquired pneumonia: a prospective cohort study

Abstract: Background Some studies previously demonstrated that interleukin-17 (IL-17) involves in pulmonary diseases progression. Nevertheless, the role of IL-17 in community-acquired pneumonia (CAP) remains unknown. This study aims to examine the correlations between serum IL-17 with the severity and prognosis in CAP patients through a prospective cohort study. Methods All 239 CAP patients were recruited. Serum IL-17 was detected by enzyme-linked immunosorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
2
19
0
Order By: Relevance
“…The results are a significant difference in the levels of IL-17A from a gradual decrease among the different groups, a greater priority than the moderate and severe groups group, and moderate group higher than severe group, this is confirmed by Ghazavi et al, (2021), there are studies that indicated an increase in IL-17A in patients with SARS-CoV-2 [20], but they did not indicate the type of severity such as: [21,22,23].…”
Section: Role Of Il-17a In Severity Sars-cov-2mentioning
confidence: 89%
See 1 more Smart Citation
“…The results are a significant difference in the levels of IL-17A from a gradual decrease among the different groups, a greater priority than the moderate and severe groups group, and moderate group higher than severe group, this is confirmed by Ghazavi et al, (2021), there are studies that indicated an increase in IL-17A in patients with SARS-CoV-2 [20], but they did not indicate the type of severity such as: [21,22,23].…”
Section: Role Of Il-17a In Severity Sars-cov-2mentioning
confidence: 89%
“…Because it is involved in the inflammation that takes place in the airways, the potent pro-inflammatory cytokine known as IL-17A is a crucial factor in the overactivation and the overwhelming inflammatory reaction of the body's defensive system [26]. This is because it plays a role in the inflammation that takes place in the airways, According to Zhou et al, which investigations in particular shown that IL-17A has a driving role in the development include pulmonary hypertension, lung fibrosis, emphysema, acute lung injury, patients diagnosed with ARDS had elevated levels of IL-17A in their serum [27,28].…”
Section: Il-1β Il-17 Il-18mentioning
confidence: 99%
“…For studying serum biomarkers, fasting blood specimens from CAP patients were collected before intervention or treatment ( 28 , 29 ). Moreover, demographic information and clinical characteristics were obtained from the electronic medical record system in the hospital ( 30 , 31 ). The severity of CAP was evaluated through CAP severity scores (CURB-65, CRB-65, SMART-COP, PSI, CURXO, and APACHE II) ( 32 , 33 ).…”
Section: Methodsmentioning
confidence: 99%
“…Taking KL-6 as an example, the serum was centrifuged to obtain the supernatant and diluted at 1: 100 in bovine serum albumin (BSA) to prepare the testing sample. A commercial enzyme-linked immunosorbent assay (ELISA) kit (Abebio, AE36646HU) was used, and the detailed protocol was as described previously [22,23]. Briefly, the test and standard samples were added to antibody-coated 96-well plates and incubated at 37 °C for 2 h. After washing with PBST, the secondary antibody was added, and then the detection solution was added.…”
Section: Laboratory Examinationmentioning
confidence: 99%